2010
DOI: 10.1159/000320752
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-3 mRNA: A Promising Peripheral Blood Marker for Diagnosis of Endometriosis

Abstract: Background/Aims: Endometriosis is an invasive disease. Its diagnosis depends on laparoscopy, which is traumatic and associated with potential complications. The aim of this study was to develop a rapid, reliable, and less invasive diagnostic test for endometriosis. We hypothesized that genes related to cell invasion would be transcriptionally upregulated in endometriosis, and tested whether blood levels of their transcripts might be used as biomarkers of endometriosis.Methods:We used quantitative real-time rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…Laparoscopic surgery is currently the first choice for the diagnosis and treatment of infertility in patients with endometriosis [6], although researchers have found some genes suitable for diagnostic quantitative RT-PCR for endometriosis in the peripheral blood [7,8]. A meta-analysis of two trials has demonstrated the advantage of laparoscopic surgery for early-stage endometriosis compared with diagnostic laparoscopy in regard to ongoing pregnancy at 20 weeks (odds ratio, 1.64; 95% confidence interval: 1.05-2.57) [9].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery is currently the first choice for the diagnosis and treatment of infertility in patients with endometriosis [6], although researchers have found some genes suitable for diagnostic quantitative RT-PCR for endometriosis in the peripheral blood [7,8]. A meta-analysis of two trials has demonstrated the advantage of laparoscopic surgery for early-stage endometriosis compared with diagnostic laparoscopy in regard to ongoing pregnancy at 20 weeks (odds ratio, 1.64; 95% confidence interval: 1.05-2.57) [9].…”
Section: Discussionmentioning
confidence: 99%
“…This model achieves the highest sensitivity and specificity. Furthermore, some researchers advise that in patients with an undiagnosed tumor in the pelvis, the CA125/CEA ratio may be used to preoperatively identify a substantial fraction of patients with ovarian and non-ovarian malignancies (15) , and confirm again that combination of serum tumor markers could improve ovarian cancer diagnosis (16,17) .CA125 is an antigenic determinant found in benign and malignant conditions Causes of Elevated CA125 Levels:…”
Section: Tumor Markersmentioning
confidence: 99%
“…The study of the character of MMPs production at the level of ectopic endometrium had shown that MMP-2 and MMP-3 overexpression were related to the infiltrative nature of endometriotic lesion (Uzan et al, 2004). It was also shown that circulating mRNA for MMP-3 was significantly higher in peripheral blood of patients with endometriosis than in control patients, regardless of the degree of endometriosis severity (De Sanctis et al, 2011). In a prospective, blinded, longitudinal study MMP-2 and MMP-9 were more likely to be detected in the urine of patients with endometriosis than in controls (Becker et al, 2010).…”
Section: Changes Of the Invasiveness Of Endometrium In Endometriosismentioning
confidence: 99%